Short-time particle motion in strong standing electromagnetic wave - Bashmakov, V.F.; Bashmakov, V.F.; Nerush, E.N.; Kostyukov, I.Yu. (Вопросы атомной науки и техники, 2013)
The particle motion in the standing electromagnetic wave was investigated on the times much shorter than the wave period. Cases of circular and linear polarizations are considered. The first nonvanishing coefficients in the series expansion of the particle momentum and particle energy are obtained. The inefficiency of energy gain in the “magnetic” region of LP wave was demonstrated. Досліджено рух частинки в стоячій електромагнітній хвилі на часових проміжках, які набагато коротші ніж період хвилі. Розглянуто випадки циркулярної та лінійної поляризацій. Отримано перші незникаючі коефіцієнти в розкладі імпульсу та енергії частинки. Продемонстрована неефективність збільшення енергії в «магнітній» області хвилі лінійної поляризації. На временах много короче, чем период волны, исследовано движение частицы в стоячей электромагнитной волне. Рассмотрены случаи циркулярной и линейной поляризаций. Получены первые неисчезающие коэффициенты в разложении импульса и энергии частицы. Продемонстрирована неэффективность увеличения энергии в «магнитной» области волны линейной поляризации.